Microbiological profile and treatment outcome of emphysematous pyelonephritis: experience from two teaching hospitals of Bangladesh - Chowdhury, Juli; Biswas, Nirmol Kumar; Kanta, Shamima Sharmin; Rahim, Muhammad Abdur; Haque, Wasim Md Mohosin Ul; Iqbal, Sarwar; Uddin, Khawja Nazim (BIRDEM Medical Journal, 2021)
Background: Emphysematous pyelonephritis (EPN) is a rare severe necrotizing infection of the renal parenchyma, collecting system and/or perirenal tissues. Patients with diabetes mellitus, renal stones and renal tract obstruction are at risk for development of EPN. Escherichia coli is the most common aetiological agent and treatment is aimed at infection control and interventions in appropriate cases. This study aimed to identify the aetiological agents responsible for EPN and the outcome of such cases. Methods: This observational study was done in BIRDEM General Hospital and Bangabandhu Sheikh Mujib Medical University over a period of three years (2011-2013). Twenty adult EPN cases were included in this study. Results: The mean age of the study participants was 59.2 years with female predominance (80%). Risk factors included diabetes mellitus (90%), renal stones (5%) and kidney transplant recipient (5%). Fever, loin pain and dysuria were common. Six patients had class 1 EPN, seven had class 2 disease, five had class 3 and two patients had class 4 EPN. Aetiological agents were cultured in 19 cases; E. coli in 12 (68%), Klebsiella in three (16%), Pseudomonus in two (11%) and Proteus and Enterococcus, one each (5% each). Carbapenems appeared as the most sensitive antibiotic. Along with antibiotic, half of the patients required interventions; percutaneous drainage in two, open drainage in two and six patients required nephrectomy. Regarding outcome, five patients died, 10 patients recovered completely and five patients recovered with residual renal dysfunction. Conclusion: E. coli was the most common causative agent in present EPN cohort. Outcome was poor. With improved management strategy, combining nephrologists, intervention radiologists and urologists – all together, a good outcome is expected. Birdem Med J 2021; 11(2): 108-111